Extramedullary plasmacytoma of the ureter in an HIV-positive patient - Nagai, Takashi (Int Cancer Conf J, 2017)
A 45-year-old Japanese man, who was undergoing HIV infection treatment, was aware that he had gross hematuria, and he was diagnosed as having a ureteral tumor by radiographic examination. Therefore, he was referred to our department for further examination and treatment. We considered that the ureteral tumor was a urothelial carcinoma (cT2N0M0) because of the left ureteral tumor and urine cytology results, and thus, laparoscopic ureteronephrectomy was performed. The pathological diagnosis was a solitary extramedullary plasmacytoma (EMP) of the ureter. Currently, he is alive and free of disease at 7 months postoperatively. EMP develops in the nasal cavity, paranasal cavity, gastrointestinal tract, lung, thyroid, eye socket, lymph node, and various organs, but the ureter is an extremely rare site of EMP. In addition, the patient had an HIV infection. To the best of our knowledge, this is the first case of EMP of the ureter in an HIV-positive patient.